(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The following article seeks to address the issue of the way local reception of the broadcasting of films in Chilean television, between 1965 and 1978, allows us to replicate and endure, the delay and anachronism of a broader historical imaginary cycle, determined, internally, by the development and illustrated project of an educational State; externally, by a residual representation of the modern heroic regimes, and in general, by the images of westernness, composed by secondary formats, such as TV series, the historical essay and cartoons. We propose to analyse and account for the diverse and nurturing implications of this ‘replication’, in the fields of aesthetics and the symbolic rewriting of the world´s representation.